The Effects of Import Tariff on Demand and Farm Productivity of Soybean Industry in Indonesia - Suminartika, Eti (2008)
Soybean industry plays an important role in the Indonesian economy. For many years, the country has an excess demand of soybean. Indonesian government has chosen to import soybean to meet the shortage of the domestic supply. However, the import has increased rapidly over the years. This dependency has become a serious problem in maintaining food security in the country. The general objective of this study is to investigate why the domestic demand of soybean relies on the imported soybean. Further, there are four specific objectives. First, this study attempts to determine factors that affect to the import demand of soybean. Second, it is carried out to analyze the effect of import tariff on the soybean industry in the country. Third, it is an attempt to estimate the producers’ surplus and lastly, it is done to analyze the productivity of soybean farming in the country. In this study, the market model of soybean industry, estimated by the two stages least squares method is used to determine factors that affect the import demand of soybean. The model is simulated by increasing import tariff so that its effect on soybean industry can be measured. Tariff has an effect on welfare, so the producer surplus’ analysis is carried out to estimate the producer’s net gain. Finally, this study uses the Total Factor Productivity (TFP) analysis in order to determine the productivity growth of the soybean farming. The results of this study show that increases in income and price of corn (substitute commodity) lead to a rise in import demand. On the other hand, an increase in import tariff will cause import demand to decline. As import demand declines, the price of soybean will rise, resulting in an increase in domestic production. Moreover, an increase in tariff will increase the producers’ welfare. Lastly, there was some evidence of growth in TFP of soybean farming in Indonesia during the period of analysis, particularly in the non-Java regions. As the growth was found to be contributed by technological progress, the government should develop these regions by improving the related farming technology (seed, fertilizer and pesticide).